Current Strategies for Monitoring and Control of IAQ - Agarwal, Renu; Kumar, Ravi (Journal for Research in Applied Sciences and Biotechnology, 2024)
The focuses of this paper is on the critical importance of indoor air quality (IAQ) and the need for innovative monitoring systems to enhance occupants' quality of life while balancing energy efficiency. Development of Materials for IAQ Sensors , Enhanced Sensitivity and Selectivity, Miniaturization and Integration, Wireless Connectivity and IoT Integration,Long-Term Stability and Reliability, Cost-Effectiveness and Scalability, Air Purification Technologies for IAQ Improvement, HEPA Filtration, Ionic Air Purification, Photocatalytic Oxidation (PCO), Electrostatic Precipitation, Hybrid Air Purification Systems, Smart Home for IAQ Control Sensor Technology, Data Analytic, Automated Ventilation, Air Filtration and Purification, Smart Thermostats and HVAC Controls, Mobile Apps and User Interfaces,Integration with Smart Home Ecosystems, Air Purification Technologies for IAQ Improvement, . Smart Home for IAQ Control. These strategies collectively empower individuals and building managers to monitor, analyze, and optimize indoor air quality, leading to healthier indoor environments. The use of advanced materials, innovative sensors, and smart technologies enables real-time data-driven decisions, promoting sustainable and effective IAQ management. The overall aim is to mitigate the risks associated with indoor air pollution and ensure that indoor environments remain clean, safe, and healthy for occupants. Ongoing research and technological advancements continue to drive progress in this important field, making IAQ management increasingly accessible and effective for diverse settings and populations.